Association of the retinal vasculature, intrathecal immunity, and disability in multiple sclerosis - Noll, Christina; Hiltensperger, Michael; Aly, Lilian; Wicklein, Rebecca; Afzali, Ali Maisam; Mardin, Christian; Gasperi, Christiane; Berthele, Achim; Hemmer, Bernhard; Korn, Thomas; Knier, Benjamin (Frontiers in Immunology, 2022)
Background: Optical coherence tomography angiography (OCT-A) is a novel technique allowing non-invasive assessment of the retinal vasculature. During relapsing remitting multiple sclerosis (RRMS), retinal vessel loss occurs in eyes suffering from acute optic neuritis and recent data suggest that retinal vessel loss might also be evident in non-affected eyes. We investigated whether alterations of the retinal vasculature are linked to the intrathecal immunity and whether they allow prognostication of the future disease course. Material and methods: This study includes two different patient cohorts recruited at a tertiary German academic multiple sclerosis center between 2018 and 2020. A total of 90 patients with RRMS undergoing lumbar puncture and OCT-A analysis were enrolled into a cross-sectional cohort study to search for associations between the retinal vasculature and the intrathecal immune compartment. We recruited another 86 RRMS patients into a prospective observational cohort study who underwent clinical examination, OCT-A and cerebral magnetic resonance imaging at baseline and during annual follow-up visits to clarify whether alterations of the retinal vessels are linked to RRMS disease activity. Eyes with a history of optic neuritis were excluded from the analysis. Results: Rarefication of the superficial vascular complex was linked to higher frequencies of activated B cells and higher levels of the pro-inflammatory cytokines interferon-γ, tumor necrosis factor α and interleukin-17 in the cerebrospinal fluid. During a median follow-up of 23 (interquartile range 14 - 25) months, vessel loss within the superficial (hazard ratio [HR] 1.6 for a 1%-point decrease in vessel density, p=0.01) and deep vascular complex (HR 1.6 for a 1%-point decrease, p=0.05) was associated with future disability worsening. Discussion: Optic neuritis independent rarefication of the retinal vasculature might be linked to neuroinflammatory processes during RRMS and might predict a worse disease course. Thus, OCT-A might be a novel biomarker to monitor disease activity and predict future disability.